The definition of sales managers management strategy - Rozumey, Svitlana; Nujna, Y. (My University, 2013)
This paper defines the components performance of sales manager, manifested by assessing the loyalty and efficiency of its operations. Thus we can estimate the level of eligibility and determine the strategy management of sales managers.
Keywords: менеджер зі збуту; оцінювання лояльності менеджера; оцінювання результативності менеджера; менеджер по сбыту; оценка лояльности менеджера; оценки результативности менеджера; sales manager; loyalty manager evaluation; manager performance evaluation; кафедра маркетингу